NEED OF LIFE SKILL EDUCATION FOR PROSPECTIVE TEACHERS - REKHA, CHITER; KUMAR, MANOJ (THE PRIMARY TEACHER, 2013)
A skill is the knowledge and ability that enables us to do something well. We all continuously use various types of skills in our daily routine life. Sometimes we use many skills very effectively to solve the problems, taking decisions, etc. in different situations, or sometimes we display inappropriate behaviour and we do not know how to use a particular skill in an effective, proper and appropriate way in a specific situation. These types of behaviours are not harmful for one who express it and for others too. We all have two types of life skills (1) Natural life skills, and (2) learned life skills. We get natural life skills by birth from our heredity whereas skills those are learned by us from our environment or society through experiences are called learned life skills. We can learn these skills in a formal or non-formal way through our environment or through various incidents. Learning how to use them effectively and continuously will help us to deal with the situation more effectively. Knowledge regarding the life skills is essential for a teacher dealing with students. This article describes the types, importance, need and significance of life skills education for prospective teachers and discusses the various strategies and methodologies to impart life skill education among prospective teachers. This information will help to understand the need of life skills education.